Mixed plastics recycling technology - Hegberg, Bruce A. (Noyes Data Corp., 1992)
This book presents an overview of mixed plastics recycling technology. In addition, it characterizes mixed plastics wastes, and describes collection methods, costs and markets for reprocessed plastics products.
Keywords: Plastics industry and trade -- United States.; Plastic scrap -- Recycling -- United States.; elektronické knihy; electronic books